PERAN GERAKAN NASIONAL NON TUNAI (GNNT) DALAM MENDORONG PERCEPATAN CASHLESS SOCIETY DI INDONESIA - Qanaya Bintang Santoso (Prodi Pendidikan Ekonomi Universitas Mulawarman, 2025)
This study aims to analyze the effect of inflation and investment on economic growth in Indonesia. Inflation and investment are macroeconomic factors that affect Indonesia's economic growth. The study used a quantitative approach to the type of descriptive research. The Data used is secondary time series data for the period 2018-2022 obtained from the Central Statistics Agency (BPS), Bank Indonesia, and various supporting sources, then analyzed using multiple linear regression. The results showed that inflation has a negative relationship with economic growth, while investment has a positive and significant effect on economic growth. Simultaneously, both variables affect economic growth with Adjusted R Square value of 42.4%, while the rest are influenced by other variables outside the study. Therefore, inflation control and increased investment needs to continue to be carried out to support Indonesia's sustainable economic growth.